Some Considerations on Secession and Independence: The Cases of Kosovo and Georgia - Stephen Neff (Amsterdam Law Forum, 2009)
Stephen P. Neff distinguishes two ‘roads to the creation of a new state by way of secession’: the ‘high road’ – which sees secession and independence as a positive right - and the ‘low road’ – which sees independence as a remedy for a delict committed by the ‘mother state’. Along these lines, Neff discusses Kosovo, Abkhazia and South Ossetia, while placing them in the broader temporal and political context. Neff draws from this discussion the conclusion that international law supports only the negative route to independence and not the positive one.